Cultivating a sustainable future: an implementation case study of permaculture and digital technologies in managed farm services context - Thampy, Sarin (IE University, 2024)
Industrial agriculture's detrimental environmental impact and the growing global demand for food necessitate sustainable agricultural practices. The current study aims to investigate the economic performance and sustainability outcomes of implementing permaculture practices and digital technologies in a managed farm services context in India (two distinct farm types: agroforestry and lifecentric farms), contributing to the growing body of knowledge on sustainable agriculture and highlighting the potential of different implementation approaches to transform the agricultural sector. A mixed-method sequential research design is used, beginning with qualitative interviews conducted with five experts associated with the single case study organization, Hosachiguru, a leading Indian farming company offering managed farm services, followed by quantitative surveys with 208 farmers (108 from agroforestry and 100 from lifecentric farms). Findings reveal that implementing permaculture practices like rainwater harvesting (mean = 4.64) and water management systems (mean = 4.63), alongside digital technologies like IoT-based moisture management (mean = 4.48) and drip irrigation (mean = 4.52), enhances both economic performance and sustainability outcomes according to the farmers. Notably, lifecentric farmers received higher benefits from certain permaculture practices (e.g., mulching, with a statistically significant difference of p < 0.001) and the MyFarm mobile app (p < 0.01) compared to agroforestry farmers. Moreover, farmers prioritized non-price factors like concept representation (mean = 4.25), amenities & facilities (mean = 4.08) and developer reputation (mean = 4.05) when purchasing managed farm services, over price (mean = 3.13). The study’s findings underscore the transformative potential of integrating permaculture and digital technologies in diverse farming contexts. Policymakers and educators should develop supportive policies and training for sustainable and digital farming. The study also provides future research directions such as effect of tailored approaches for sustainable agriculture and the need for a longitudinal study to track improvements over time among others
CULTIVANDO UN FUTURO SOSTENIBLE: UN ESTUDIO DE CASO SOBRE LA IMPLEMENTACIÓN DE LA PERMACULTURA Y TECNOLOGÍAS DIGITALES EN EL CONTEXTO DE SERVICIOS AGRÍCOLAS GESTIONADOS
El impacto ambiental perjudicial de la agricultura industrial y la creciente demanda global de alimentos hacen necesarias prácticas agrícolas sostenibles. El presente estudio tiene como objetivo investigar el rendimiento económico y los resultados de sostenibilidad de la implementación de prácticas de permacultura y tecnologías digitales en el contexto de servicios agrícolas gestionados en la India (en dos tipos distintos de granjas: agroforestales y granjas centradas en la vida). Con ello, se contribuye al creciente cuerpo de conocimiento sobre la agricultura sostenible y se destacan los diferentes enfoques de implementación con el potencial de transformar el sector agrícola. Se emplea un diseño de investigación secuencial con enfoque mixto, comenzando con entrevistas cualitativas a cinco expertos vinculados con la organización de objeto del estudio de caso, Hosachiguru, una destacada empresa agrícola India que ofrece servicios de gestión de granjas. Posteriormente, se aplicaron encuestas cuantitativas a 208 agricultores (108 de granjas agroforestales y 100 de granjas centradas en la vida). Los hallazgos revelan que la implementación de prácticas de permacultura, como la cosecha de agua de lluvia (media = 4.64) y los sistemas de gestión del agua (media = 4.63), junto con tecnologías digitales como la gestión de humedad basada en IoT (media = 4.48) y el riego por goteo (media = 4.52), mejora tanto el desempeño económico como los resultados de sostenibilidad, según los agricultores. En particular, los agricultores de las granjas centradas en la vida obtuvieron mayores beneficios de ciertas prácticas de permacultura (por ejemplo, el acolchado, con una diferencia estadísticamente significativa de p < 0.001) y de la aplicación móvil MyFarm (p < 0.01) en comparación con los agricultores de granjas agroforestales. Además, al adquirir servicios agrícolas gestionados, priorizaron factores no relacionados con el precio, como la representación del concepto (media = 4.25), las comodidades e instalaciones (media = 4.08) y la reputación del desarrollador (media = 4.05), por encima del precio (media = 3.13). Los hallazgos del estudio subrayan el potencial transformador de la integración de la permacultura y las tecnologías digitales en diversos contextos agrícolas. Se recomienda que los responsables de políticas y educadores desarrollen normativas y programas de capacitación que respalden la agricultura sostenible y digital. Además, el estudio sugiere futuras líneas de investigación, como el impacto de enfoques personalizados en la agricultura sostenible y la necesidad de un estudio longitudinal para evaluar mejoras a lo largo del tiempo, entre otros aspectos.